Ébola - da ignorância ao medo ou a maior crise aguda de saúde pública nos últimos 50 anos - Antunes, Francisco (2015)
One year since the begin of Ebola virus disease (EVD) outbreak in West Africa, the worst Ebola epidemic in history is ongoing. The epidemic began in Guinea during December 2013 and expanded to Sierra Leone and Liberia. The first cases of EVD, previously designated Ebola haemorrhagic fever were reported in 196F. Similar cases of haemorrhagic fever were described in 1976 from outbreaks in Sudan and Zaire. Five distinct species of Ebola virus were described (Sudan, Zaire, Tai Forest, Bundibuyo and Reston), and EVD remains a plague for the population of equatorial Africa. Almost all human cases are due to Sudan and Zaire Ebola virus. EVD is thought to be a classic zoonosis with persistence of the Ebola virus in a reservoir species, generally bats. Apes and man are regarded as end hosts. Human-to-human transmission leads to outbreaks, and EVD is spread mainly through the contact of body fluids of patients and cadavers. EVD follows an incubation period of 2-21 days and is characterized by fever, vomiting and severe diarrhea, having case-fatality rates of 50-80%. Ebola virus has a broad cell tropism with release of cytokines and other proinflamatory cellular mediators, leading to multiorgan failure. There is currently no licensed prophylaxis or treatment for EVD; therefore, treatment is merely supportive. The diagnostic of EVD is suspected in a patient with fever, and other main clinical manifestations of EVD, who have risk exposure to the Ebola virus inside or outside the geographic areas of EVD. Laboratory diagnosis is achieved primary by detection of viral particles, or particle components (PER and antigen detection ELISA) and secondary by measurement of host-specific immune response to infection (a IgM or rising IgG titre constitutes a presumptive diagnosis). Ease management is based on isolation of patients and strict barrier nursing procedures. In Africa, traditional funerals and caretaking methods contribute to the spread of the virus and potentiate outbreaks, and should be handled according to avoid the risk to Ebola virus exposure.